1998
DOI: 10.1038/sj.ijo.0800726
|View full text |Cite
|
Sign up to set email alerts
|

Dietary manipulation and energy compensation: does the intermittent use of low-fat items in the diet reduce total energy intake in free-feeding lean men?

Abstract: OBJECTIVE: The effect of two low-fat treatments on ad libitum energy intake (EI) was investigated in ®ve lean men living within a metabolic facility. DESIGN: Diet was controlled over two consecutive periods of 12 d when either, i) all foods eaten or ii) only a single (lunch) meal, was manipulated to increase the fat content from 20, 40 to 60% of energy, and ad libitum EI measured. RESULTS: All foods: EI increased from 8.6 (2.9 s.d.) ± 14.8 (3.1 s.d.) MJad and energy density (ED) from 4.1 (0.8 s.d.) ± 7.7 (1.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…6 For example, in a recent study that controlled for the potential effect of both macronutrient composition and palatability, Bell concluded that energy intake was driven by the energy density of the meals provided. 9 A series of investigations using covert manipulations of energy density and macronutrient composition 7,19,24 and general reviews of the issue 10,19 have arrived at similar conclusions.…”
Section: Discussionmentioning
confidence: 80%
“…6 For example, in a recent study that controlled for the potential effect of both macronutrient composition and palatability, Bell concluded that energy intake was driven by the energy density of the meals provided. 9 A series of investigations using covert manipulations of energy density and macronutrient composition 7,19,24 and general reviews of the issue 10,19 have arrived at similar conclusions.…”
Section: Discussionmentioning
confidence: 80%
“…Most studies on ED have been based on individual foods, single dishes, or single meals (5,6), although a few have addressed the ED of the total diet (42)(43)(44). Dietary ED is difficult to establish because there is little consensus concerning whether water, noncaloric beverages, caloric beverages, soups, semiliquids, or semisolids ought to be included or excluded from analyses.…”
Section: Ed Of the Dietmentioning
confidence: 99%
“…The increasing prevalence of overweight and obesity has prompted study of the contributory role played by dietary fat (1, 2, 3, 4, 5, 6, 7). One line of evidence indicates that fat's high energy density and palatability contribute to passive overconsumption (8, 9); that is, fat holds weak satiating and satiety properties (10, 11).…”
Section: Introductionmentioning
confidence: 99%